Effects of feed delivery frequency in different environmental conditions on time budget of lactating dairy cows. Issue 3 (23rd August 2017) - Mattachini, Gabriele; Bava, Luciana; Sandrucci, Anna; Tamburini, Alberto; Riva, Elisabetta; Provolo, Giorgio
Abstract : This study aimed to examine the influence of feed delivery frequency and environmental conditions on daily time budget of lactating dairy cows. The study was carried out in two commercial dairy farms with Holstein herds. Fifty lactating dairy cows milked in automatic milking units (AMS farm) and 96 primiparous lactating dairy cows milked in a conventional milking parlour (conventional farm) were exposed to different frequencies of feed delivery replicated in different periods of the year (warm and mild) that were characterized by different temperature-humidity indices (THI). On each farm, feeding treatments consisted of two different feed delivery frequencies (1× and 2× on the AMS farm; 2× and 3× on the conventional farm). All behaviours of the cows were monitored for the last 8 d of each treatment period using continuous video recording. The two data sets from different farm systems were considered separately for analysis. On both farms, environmental conditions expressed as THI affected time budgets and the pattern of the behavioural indices throughout the day. The variation in the frequency of feed delivery seems to affect the cow's time budget only in a limited way. Standing time of cows on the conventional farm and the time spent by cows in the milking waiting area on the AMS farm both increased in response to increased feeding frequency. Although feed delivery frequency showed limited influence on cow's time budget, the effect on standing time could be carefully considered, especially on farms equipped with AMS where the type of cow traffic system (e.g., milking first) might amplify the negative consequences of more frequent feed delivery. Further investigations are required to evaluate the effect of THI and feed delivery frequency on other aspects of behavioural activity.